Effects of lupeol and flutamide on experimentally-induced polycystic ovary syndrome in mice - Ali Rezaei-Golmisheh; Rajabali Sadrkhanloo; Abbas Ahmadi; Hassan Malekinejad (Iranian Journal of Basic Medical Sciences, 2024)
Objective(s): Polycystic ovary syndrome (PCOS) is one of the main causes of infertility in women. This study was conducted to uncover the effects of lupeol as an anti-androgenic triterpene on experimentally-induced PCOS in mice. Materials and Methods: Eighty immature female mice were divided into 4 groups: Control (C), PCOS (P), Lupeol (L), and Flutamide (F). PCOS was induced in test groups by injection of Dehydroepiandrosterone (60 mg/kg/day, IP) for twenty days. Following the PCOS induction, the two groups of L and F were treated with lupeol (40 mg/kg/day) and/or flutamide (10 mg/kg/day) respectively and the two groups of C and P received sesame oil (0.1 ml/mouse/day) for 15 days. After the treatment period, ten animals in each group were selected for collecting blood and ovary samples. In vitro  fertilization assessment was carried out on 10 remaining mice in each group. The hormonal assays and oxidative stress biomarker determination were performed on serum and tissue samples. Moreover, histopathological analyses were conducted on the ovaries.Results: PCOS-elevated concentration of LH and Testosterone was significantly (P<0.05) lowered in lupeol and flutamide-received animals. Lupeol and flutamide both reduced PCOS-induced fibrosis and the number of atretic follicles. Both compounds declined the PCOS-increased lipid peroxidation and protein oxidation in serum and the ovaries. Lupeol increased the PCOS-reduced fertility rate and decreased the number of arrested embryos by 12%. Conclusion: These findings indicate that lupeol could be a novel compound in the treatment of PCOS as it reduced PCOS-induced structural and also functional disorders.